2019
DOI: 10.1111/jnc.14823
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase – a regulator of canonical transient receptor potential channel 6 (TRPC6) activity

Abstract: Recent investigations propose the acid sphingomyelinase (ASM)/ceramide system as a novel target for antidepressant action. ASM catalyzes the breakdown of the abundant membrane lipid sphingomyelin to the lipid messenger ceramide. This ASM‐induced lipid modification induces a local shift in membrane properties, which influences receptor clustering and downstream signaling. Canonical transient receptor potential channels 6 (TRPC6) are non‐selective cation channels located in the cell membrane that play an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
5
10
0
Order By: Relevance
“…Thus, both systems seem to be interconnected. Our earlier study in a neuronal cell line included data on FIASMA-mediated impaired TRPC6 function that was rescued by the application of bacterial sphingomyelinase [33]. Therefore, we thought ASM WT glial cells would be able to rescue the impaired TRPC6 function in ASM KO neurons with the secretion of ASM from WT glia to KO neurons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, both systems seem to be interconnected. Our earlier study in a neuronal cell line included data on FIASMA-mediated impaired TRPC6 function that was rescued by the application of bacterial sphingomyelinase [33]. Therefore, we thought ASM WT glial cells would be able to rescue the impaired TRPC6 function in ASM KO neurons with the secretion of ASM from WT glia to KO neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we have demonstrated an interaction between ASM activity and TRPC6 function in rat pheochromocytoma 12 (PC12) cells. However, the link between TRPC6 and ASM remained correlative [33]. Therefore, in this study, we investigated the function of TRPC6 channels in neurons derived from ASM deficient mice (ASM KO) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Vice versa, when sphinogomyelin hydrolysis was driven by treating hippocampal slices with neutral sphingomyelinase (NSM), Norman et al (2010) observed an increased excitability of CA1 pyramidal cells through a S1Pmediated mechanism. Finally, a recent study demonstrated that ASM modulates the biophysical properties of TRPC6 activity by controlling the interaction of TRPC6 channels with specific lipid subdomains (Zeitler et al, 2019). The apparent multitude of ion channels, whose gating characteristics as well as surface expression may be affected by S-ASM, may account for the different types of altered firing patterns in response to acute ASM inhibition that we observed in ARC39treated neurons (Figures 4, 5).…”
Section: Discussionmentioning
confidence: 65%
“…These differential effects suggest that counterregulation of RNA levels restores Asm activity levels. Balanced Asm activity is essential for proper functioning of the cell [ 41 ], and it is possible that Smpd1 mRNA expression is upregulated as soon as cellular Asm activity decreases to a specific level to maintain optimal conditions. However, this regulatory effect was not evident in primary human blood cells; both 24 h and 48 h after fluoxetine stimulation, ASM activity and SMPD1 mRNA expression were reduced by approximately 80% as compared with control conditions.…”
Section: Discussionmentioning
confidence: 99%